First-generation total ankle arthroplasty: a 39-year-old case - Afonso, Carolina Tiago; Andrade, António José Pereira de; Freitas, Miguel Martins Pereira Pinto de; Ruano, Afonso Salgado (Scientific Journal of the Foot & Ankle, 2019)
Ankle prostheses are a source of disagreement within the orthopedic community due to the poor initial results. The lack of alternatives to arthrodesis has promoted the evolution of arthroplasties. Biomechanical compatibility has been improved, new surgical techniques and instrumentation devices have been developed, and biological techniques for fixation of the various components have been introduced. The first-generation arthroplasty prostheses introduced in the 1970s were cemented and had a stable constrictive design, but because they required extensive bone resection for implantation, they failed due to loosening and extensive osteolysis. We report a case of left total ankle arthroplasty performed in 1980 that is still “in situ”. Based on the bibliographic research performed, this case seems to represent the longest-lasting implant reported to date. Level of Evidence V; Therapeutic Studies; Expert Opinion.